2021
DOI: 10.1177/2473011421993793
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2 Oblique Fifth Metatarsal Osteotomies for the Management of a Bunionette

Abstract: Background: A bunionette is a painful prominence of the fifth metatarsal head. This study aimed to compare the clinical outcome of 2 corrective osteotomies, namely, the Mau-type and Ludloff-type osteotomies. We report results with regard to correction, healing, complications, and patient-reported outcomes. Methods: Thirty-two patients who underwent bunionette corrective surgery from March 2011 to May 2017 were included in the study. All patients had pre- and postoperative radiographs. The pre- and postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(63 reference statements)
1
2
0
Order By: Relevance
“…Some authors have suggested diaphyseal and proximal osteotomies to correct types II and III. 22 , 28 The results of the present study showed a significant reduction in IMA, foot width, and LDA, suggesting that our technique is sufficient to correct all types of bunionette. In our opinion and according to what was published by Ferreira et al, 8 the reduction of the lateral prominence of the fifth metatarsal generates great satisfaction in patients after surgery.…”
Section: Discussionsupporting
confidence: 56%
“…Some authors have suggested diaphyseal and proximal osteotomies to correct types II and III. 22 , 28 The results of the present study showed a significant reduction in IMA, foot width, and LDA, suggesting that our technique is sufficient to correct all types of bunionette. In our opinion and according to what was published by Ferreira et al, 8 the reduction of the lateral prominence of the fifth metatarsal generates great satisfaction in patients after surgery.…”
Section: Discussionsupporting
confidence: 56%
“…The overall rate of revision surgery ranges between 0% and 13.6%. 5,12,18,28,33,39,42 Our study showed a revision rate of 1.35%. One patient needed an additional procedure to resect a lateral prominent bone associated with HDC.…”
Section: Discussionmentioning
confidence: 46%
“…These are related to stress fractures, dorsal angulation of the fifth toe, wound disorders, and osteosynthesis intolerance, among others. 17,18,21,29,32,39,42,56 These data are crucial when choosing the operative procedure. This confirms that minimally invasive surgery techniques have good results in general and would be an excellent choice for BD treatment.…”
Section: Discussionmentioning
confidence: 99%